First report of Nattrassia mangiferae root and stem rot of cassava in West Africa - Msikita, W.; Yaninek, John S.; Ahounou, M.; Baimey, H.; Fagbemissi, R. (Scientific Societies, 1997)
During part of the dry season in 1996 (November to December), surveys were made for incidence of root and stem rot in 99 fields of cassava (Manihot esculenta Crantz) randomly selected between latitudes 6°36′N and 7°49′N in Benin (79 fields) and Nigeria (20 fields). Root rot was observed in 65 fields in Benin and 15 fields in Nigeria. Disease incidence ranged from 0 to 54%. A total of 201 samples of wilted and/or dead plants were collected for laboratory analysis. Infected root and stem portions (0.5 to 1 cm) were cut out, surface disinfested (10 min) in 10% bleach (0.6% sodium hypochlorite), rinsed in sterilized distilled water, and cultured on potato dextrose agar acidified to pH 4.5 with 0.4% (vol/vol) lactic acid. Cultures were incubated at 25°C, under 12-h day length provided by cool-white fluorescent lamps. After 1 week, mycelia, conidiophores, and conidia were observed at ×30 to ×40 magnification under a compound microscope. Out of the 169 symptomatic samples collected from Benin, nine fungal genera were isolated: Aspergillus spp. (1% of fungi observed), Botryodiplodia theobromae Pat (7.7%), Fusarium spp. (11.8%), Macrophomina phaseolina (Tassi) Goidanich (14.2%), Nattrassia mangiferae (Syd. & P. Syd.) B. Sutton & Dyko (56.2%), Penicillium spp. (0.6%), Pythium spp. (2.9%), Rhizopus spp. (1.7%), and Trichoderma spp. (2.4%). One percent of the fungi isolated did not sporulate in culture and were not identified. Out of the 32 samples collected from Nigeria, four fungal genera were identified: N. mangiferae (40.6%), B. theobromae (28.1%), M. phaseolina (18.7%), and Fusarium spp. (12.5%). Since N. mangiferae was isolated with the highest frequency, its pathogenicity was tested on cassava (cultivars Agric, Ben 86052, Dessa 88, Tchukunochi, and TMS 30572). Two weeks prior to the experiment, inocula for pathogenicity tests were prepared by incubating 5-mm-diameter mycelial plugs of N. mangiferae with 500 ml of autoclaved rice seed for 10 days at 25°C, followed by air drying in a laminar flow hood for 2 days. Five 30-cm-long stem portions were cut from healthy plants of each cassava cultivar, surface disinfested in hot water (52°C, 5 min), and transplanted into sterilized (autoclaved, 1 h) sand in 1-liter pots to which 10 ml of the N. mangiferae-colonized rice inoculum had been added. There were five control stems for each cultivar, similarly treated, but not inoculated. Plants were maintained in a greenhouse under natural light at 28 to 30°C. Thirty days after planting, plant height, lesion length, and number of shoots and roots were recorded. For all five cultivars, N. mangiferae significantly (P < 0.05) reduced plant height and number of shoots and roots, compared with control plants. Lesions (3 to 15 cm long) formed on the lower stem portions of all inoculated plants, resulting in variable degrees of wilting of the infected plants. Two of the cultivars (Agric and Ben 86052) died 3 weeks after planting. Control plants remained asymptomatic. N. mangiferae was consistently reisolated from infected plants, and the identification was independently confirmed by the International Mycological Institute, Surrey, UK. Scytalidium sp., a synamorphic state of N. mangiferae (2), was reported to cause up to 85% cassava root yield loss in South America (1). This is the first report of N. mangiferae causing cassava root and stem rot in West Africa.